Pengelasan Sprocket dengan Alat Bantu untuk Meminimalisir Kelelahan dan Meningkatkan Produktifitas di PT IMC Dengan Pendekatan Ergonomi - Ali Muthohar; Antoni Yohanes (Jurnal Serambi Engineering, 2025)
This study aims to design an ergonomic workstation and implement a rotating jig aid in the sprocket welding process at PT.IMC. The main focus is to reduce worker fatigue, improve work efficiency, and ensure welding quality. The methodology includes risk analysis using Failure Mode and Effect Analysis (FMEA), direct observation, worker interviews, biomechanical measurements, and ergonomic and productivity evaluations before and after the ergonomic aid implementation. The results indicate that the application of the rotating jig and procedural modifications significantly reduce fatigue risk by 45%, increase welding productivity by 66%, and decrease product defect rates by 100%. These findings highlight the importance of integrating ergonomic principles in manufacturing processes to enhance worker well-being and operational efficiency. Recommendations are provided for broader application in similar manufacturing industries to achieve sustainable improvements.